O papel do suporte social no trabalho e da resiliência no aparecimento de burnout: um estudo com bombeiros militares - Lopes, Vanessa Rodrigues (2010)
The firefighters have been mentioned to be vulnerable professionals to the development of the burnout syndrome as the result of a great load of emotional tension and also physical and mental stress. However, there might have some factors that protect these professionals by predicting the occurrence of the burnout, among which we highlight resilience and social support. In order to investigate this relationship, the purpose of this research was to evaluate the potential predictive power of social support at work on resilience, and its power on predicting the appearance of the burnout syndrome in military firefighters. The study included 361 firefighters from Minas Gerais, mostly males (95.8%), average age 35 (SD = 6.8 years), high school graduated (47.9%), mostly married or in stable relationships (69.8%). The data collection tools were: socio-demographic questionnaire, Escala de Caracterização do Burnout (ECB), Escala de Percepção de Suporte Social no Trabalho (EPSST); and Connor- Davidson Resilience Scale (CD-RISC-10). Multiple regression analysis were performed, as well as analysis of variance (ANOVA) and t Test. The data revealed that 10% of the firefighters find themselves with high levels of burnout, followed by 23% that present an eminent risk of developing the syndrome. Social support at work has not been confirmed as a significant resilience predictor. The three dimensions of perception of social support at work and resilience presented inverse correlations with the burnout dimensions. Regression analysis showed three highlighted variables when explaining the occurrence of burnout, they are: perception of informational support at work, resilience and age. The time in the same activity has showed a significant impact concerning exhaustion and dehumanization. Perception of emotional support at work was a meaningful predictor regarding work disappointment. The results confirmed some literature findings and showed the need to keep searching for a better understanding of these burnout predictors. The study limitations have been presented and a research agenda has been proposed in order to add information to the findings of this research.